LSD and ketanserin and their impact on the human autonomic nervous system. (27th March 2021) - Olbrich, Sebastian; Preller, Katrin H.; Vollenweider, Franz X.
Abstract: The interest in lysergic acid diethylamide (LSD) has sparked again due to its supposed positive effects on psychopathological conditions. Yet, most research focuses on the actions of LSD on the central nervous system. The interaction with the autonomic nervous system (ANS) has been neglected so far. Therefore, the aim was to assess the effects of LSD and the serotonin 2A receptor antagonist ketanserin on the ANS as assessed by heart rate variability (HRV) measures and their correlation with subjective drug‐induced effects in a randomized, placebo‐controlled crossover trial. Thus, ANS activity was derived from electrocardiogram recordings after intake of placebo, LSD or ketanserin, and LSD by calculating R‐peak‐based measures of sympathetic and parasympathetic activity. Repeated measure ANOVA and partial correlation for HRV measures and subjective experience questionnaires were performed. LSD predominantly increased sympathetic activity, while ketanserin counteracted this effect on the ANS via an increase of parasympathetic tone. Sympathetic activity was positively and parasympathetic activity negatively associated with psychedelic effects of LSD. Furthermore, Placebo HRV measures predicted subjective experiences after LSD intake. The association between trait ANS activity and LSD‐induced subjective experiences may serve as a candidate biomarker set for the effectiveness of LSD in the treatment of psychopathological conditions. Abstract : Knowledge on the impact of LSD and its antagonist ketanserin on the human autonomic nervous system is sparse. We show that the subjective effects of LSD are mainly driven by sympathetic activation and can be antagonized by ketanserin‐induced parasympathetic activity. The autonomic parameters further might serve as biomarkers for subjective LSD experiences and potentially as treatment markers, for example, in mood disorders.